FROM ROSALINE TO JULIET: ROMEO'S ROMANTIC FICKLENESS IN ROMEO AND JULIET - Saeed, Yadgar Faeq (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
In William Shakespeare's Romeo and Juliet, the evolution of the character of Romeo reflects a transformation from obsessive infatuation to true love, exposing the irrationality of youth and the fragility of emotions. In the beginning of the tragic drama, we find Romeo in his state of despair after being rejected by Rosaline, which only goes to confirm the shallowness and most likely temporary nature of his feelings. Only Juliet, the love of his life, can bring him to the edge of genuine and profound love. This transformation in the character of Romeo pushes the tragic story and explains the internal conflict faced by characters due to their own wishes, desires and societal expectations. The scheme of his romance with Juliet develops quickly, from their initial meeting to their instant marriage. However, this impulsiveness also leads to their downfall, as their love goes against the long-standing feud between the Montagues and Capulets. Shakespeare uses this character to show the irrationality of love and the power of forces pushing outside. The work is not confined to the analysis of romantic love and its reflection, but also looks at the strife of society that make, shape and eventually kill that love. Romeo appears as a means for Shakespeare’s parallel yet different understanding of love – its beauty and its vulnerability, compelling readers to reflect on the power of love and the conditions that allow or prohibit it.